Report of the Hospital Sub-committee - Horder, Thomas, 1871-1955 (London : Institutional Management Association)
1943-09-11 1943 1940s 15 pages INSTITUTIONAL MANAGEMENT ASSOCIATION. REPORT OF THE HOSPITAL SUB-COMMITTEE WITH a Foreword by LORD HORDER To be obtained from the Institutional Management Association 29, Gordon Square, London, W.C.1 Price 9d. post free 292/842/2/104